A nursing student's reflections in the office of the coroner. Issue 5 (3rd September 2019) - Ellingson, Rachel; Filice, Sylvane
ABSTRACT: This article is a reflection of a student's experience in a new and innovative placement in the office of a coroner in rural and remote areas of northwestern Ontario. It is a reflection on the significance of the registered nurse in this role, and how it has evolved to consider the deeply holistic, relational, and moral nature of death investigation practice for nurses. It intertwines narrative and focused literature review to enhance discussion of the significance of the role nurses can play in death investigation specifically to serve communities in Northwestern Ontario.